Vibration-induced effects caused by impact wrenches used in truck assembly - Jorulf, Lars (Scandinavian Journal of Work, Environment & Health, 1986)
The objective of the study was to evaluate the risk of developing vibration-induced white finger (VWF) and numbness during truck assembly with impact wrenches, and the method used was a cross-sectional study made with questionnaires. Of the 904 workers asked about their use of the tool, 262 were identified as "solely exposed" to impact wrenches, the mean exposure time being 6.7 years. The acceleration range was 3.9-18.1 m/s2, When the exposure dose was estimated by exposure years, a dose-response relationship existed up to the exposure class 7-9 years. In this exposure class, 23 010 were affected by VWF and 33 010 by numbness. Although the results indicate moderate vibrationinduced effects for most of the impact wrenches in use during truck assembly, the effects can be considerable for some of the tools. For the numbness symptom, confounding factor s and some other aspects may make the result more uncertain.
Keywords: impact wrench; numbness; questionnaire; truck assembly; vibration; vibration-induced effect; weighted acceleration; white finger